2010
DOI: 10.1144/0016-76492009-090
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations in biosphere 87 Sr/ 86 Sr in Britain

Abstract: Strontium isotopes are a powerful tool for investigating the geographical origins of people and animals but assignment of provenance requires reference maps and databases. This paper presents a map of strontium isotope variations across Britain for use in archaeological and other studies, and is produced by direct measurement of strontium isotope compositions of biosphere components, predominantly plants. The map characterizes the biosphere signature of specific lithologies: a technique that is applicable worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
316
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 344 publications
(338 citation statements)
references
References 28 publications
22
316
0
Order By: Relevance
“…However, in those studies, the soil-exchangeable cations were obtained using various chemical reagents, which hampers direct comparison with our results -here we simply used MilliQ water. Nonetheless, Evans and Tatham (2004) Sr/ 86 Sr. Evans et al (2010) found that the 87 Sr/ 86 Sr recorded by snail shells appears to be shifted towards that of rainwater. Furthermore, land snails also incorporate significant amounts of soil carbonates into their diet -up to 40% (Yanes et al, 2008).…”
Section: Soil Leachatesmentioning
confidence: 93%
See 2 more Smart Citations
“…However, in those studies, the soil-exchangeable cations were obtained using various chemical reagents, which hampers direct comparison with our results -here we simply used MilliQ water. Nonetheless, Evans and Tatham (2004) Sr/ 86 Sr. Evans et al (2010) found that the 87 Sr/ 86 Sr recorded by snail shells appears to be shifted towards that of rainwater. Furthermore, land snails also incorporate significant amounts of soil carbonates into their diet -up to 40% (Yanes et al, 2008).…”
Section: Soil Leachatesmentioning
confidence: 93%
“…However, the fact that 87 Sr/ 86 Sr of the intra-site ground vegetation is lower than that of the corresponding tree leaves reflects the overall lower 87 Sr/ 86 Sr found in top soils, which seems to occur regardless of the nature of the geological substrate. Although vegetation samples have been used as Sr isotope biosphere proxy (Evans et al, 2010;Kusaka et al, 2011), the constantly less radiogenic 87 Sr/ 86 Sr found in ground vegetation needs to be better understood. In particular, one must determine which type of plant, ground vegetation or tree leaves, yields the most reliable estimate of the bioavailable 87 Sr/ 86 Sr entering the food chain today and in the past.…”
Section: Soil Leachatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, interpretation is hindered by the relatively coarse biosphere maps that are generally available. The work by Evans et al (2010) has greatly improved the situation in Britain, but biosphere mapping remains far from comprehensive.…”
Section: Methodsmentioning
confidence: 99%
“…Enamel samples were cleaned with high-purity (99%) acetone followed by deionised water (DI H 2 O, > 17 MΩ) and dried down. Plant samples were washed in DI water, dried and crushed to tea leaf consistency following Evans et al (2010). Samples were then weighed into clean perfluoroalkoxy (PFA) vials.…”
Section: Methodsmentioning
confidence: 99%